2020
DOI: 10.3390/foods9050645
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins in Food and Methods of Their Determination

Abstract: Coumarin is a natural product with aromatic and fragrant characteristics, widespread in the entire plant kingdom. It is found in different plant sources such as vegetables, spices, fruits, and medicinal plants including all parts of the plants—fruits, roots, stems and leaves. Coumarin is found in high concentrations in certain types of cinnamon, which is one of the most frequent sources for human exposure to this substance. However, human exposure to coumarin has not been strictly determined, since there are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 84 publications
0
61
0
2
Order By: Relevance
“…The results of this study confirmed the findings from the previous studies on Citrus family. As evidenced by the previous studies, fruits from the Citrus, especially the peels [6], demonstrated maximal anticoagulant effect, which recommend that they have anti-thrombin component and could counteract thrombosis assuming a cardioprotective job [5,7]. As a result, excessive blood clotting can be prevented, which thereby prevents clots to travel to the brain, heart, kidneys, lungs, and extremities, which can cause heart attack, stroke, damage to the organs, or death [7,19].…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The results of this study confirmed the findings from the previous studies on Citrus family. As evidenced by the previous studies, fruits from the Citrus, especially the peels [6], demonstrated maximal anticoagulant effect, which recommend that they have anti-thrombin component and could counteract thrombosis assuming a cardioprotective job [5,7]. As a result, excessive blood clotting can be prevented, which thereby prevents clots to travel to the brain, heart, kidneys, lungs, and extremities, which can cause heart attack, stroke, damage to the organs, or death [7,19].…”
Section: Resultsmentioning
confidence: 54%
“…Citrus, as a member of the Rutaceae family, can synthesize both coumarins and furanocoumarins [3]. Previous studies revealed that citrus peel contains larger diversity and higher concentrations of coumarin or furanocoumarin than the pulp of the same fruits [5,6,7]. Coumarin derivatives are used as oral anticoagulants that inhibit vitamin K from functioning as a cofactor in the hepatic synthesis of the vitamin K-dependent coagulation factors II, VII, IX, and X [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coumarin and coumarins, its derivatives, can be found in many plants, including tonka beans (where they are present in high concentration), Cinnamon cassia and cherry blossom of the genus Prunus [ 294 ]. The use of coumarins in the prevention of ischemic stroke is based on the anticoagulant or antiplatelet effects exhibited by many of these molecules [ 295 , 296 , 297 , 298 ].…”
Section: Polyphenols and Stroke: Results From Preclinical Stroke Mmentioning
confidence: 99%
“…Coumarins display a broad range of biological and pharmacological activities, [ 5 , 6 ] such as antiviral [ 7 , 8 , 9 , 10 ], anticancer [ 11 , 12 , 13 ], antimicrobial [ 14 , 15 ], and antioxidant [ 16 , 17 , 18 ] activities. On the other hand, coumarin represents an ingredient in perfumes [ 19 ], cosmetics [ 20 ], and as industrial additives [ 21 , 22 ]. Furthermore, coumarins play a pivotal role in science and technology as fluorescent sensors, mainly due to their interesting light-emissive characteristics, which are often responsive to the environment [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%